Dyslipidemia in Type II Diabetes Mellitus Patients Presenting With Foot Ulcer - Khalid Usman, Mujeeb Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dyslipidemia constitutes one of the most common co-existing metabolic disorders in type II Diabetes Mellitus. It has a significant impact in the development of peripheral vascular disease and diabetic foot ulcers. Changes in the lipid profile promote the development of atheromas and impact microcirculation which delays healing of wounds and increases the likelihood of infections, amputations and other poor outcomes in the patient. Objectives: To assess dyslipidemia frequency and pattern as well as dyslipidemia and ulcer severity correlation among Type II diabetes patients with foot ulcers. Methodology: This cross-sectional study included 100 hospitalized patients with Types II Diabetes Mellitus and patients with diabetic foot ulcers admitted to the medical and surgical wards. Fasting lipid profiles including total cholesterol, triglycerides, HDL and LDL were obtained. Data were analyzed with SPSS version 24.0. Continuous variables were described as mean ± standard deviation and the relationship between levels of lipids and the grade of ulcers were analyzed with the chi-square test. Results: Among the 100 participants, the demographic breakdown revealed 64% as male and 36% as female, with an average age of 56.8 years and a standard deviation of 9.2 years. Dyslipidemia occurred in 72 patients. We found elevated total cholesterol levels in 58% of patients, Tri glycerol levels in 62%, low levels of HDL 69% and elevated levels of LDL cholesterol in 55%, thus all these values signify the presence of dyslipidemia. There was a statistically significant relationship between elevated Wagner ulcer grades and low HDL levels (p = 0.021). The presence of multiple dyslipidemias was predictive of prolonged ulcer and poor wound healing (p = 0.037). Conclusion: Dyslipidemia remains highly prevalent among Type II diabetic patients with foot ulcers and has been shown to have a significant association with ulcer severity. Specifically, low HDL and high triglyceride levels indicate greater dyslipidemia severity and ulcer progression. Dyslipidemia screening and early corrective measures may facilitate healing and improve ulcer management, thereby potentially ameliorating amputation incidences. Integrating lipid management with comprehensive diabetic foot care is pivotal in advancing the outcomes of these patients. Keywords: Type 2 Diabetes Mellitus; Dyslipidemias; Diabetic Foot Ulcer; Lipid Profile